Global Stability Analysis of a General Scalar Difference Equation - Merdan, Huseyin; Gumus, Ozlem Ak; Karahisarli, Gamzegul (Discontinuity, Nonlinearity, and Complexity, 2026)
We consider a general first-order scalar difference equation with and without Allee effect. The model without Allee effect represents asexual reproduction of a species while the model including Allee effect represents sexual reproduction. We analyze global stabilities of both models analytically and compare the results obtained. Numerical simulations are included to support the analytical results. We conclude that Allee effect has a destabilizing effect on the global stability of the model. This result is different from the local stability behaviour of the same fixed point of the model.